1991
DOI: 10.1152/ajprenal.1991.260.4.f602
|View full text |Cite
|
Sign up to set email alerts
|

Renal synthesis of atriopeptin-like protein in physiology and pathophysiology

Abstract: Atriopeptin is synthesized in mammalian atria as a 126-amino acid (14 kDa) prohormone, but it is secreted and circulates as a 28-amino acid (2.5 kDa) peptide. We have demonstrated the synthesis and secretion of an atriopeptin-like peptide in neonatal and adult rat kidney cell cultures. In this study, we evaluated the site of renal synthesis of this protein and its expression in normal rats and rats made nephrotic with puromycin aminonucleoside. The major form of atriopeptin in normal kidneys comigrated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The rate o f degradation o f URO is signif icantly lower than that o f CDD/ANP-99-126. a result which was confirmed by other groups [64.66] 58] These investigations may explain the differences o f tile in vivo kinetics between the two main A-type NPs. These differences, however, concern results described for long-term infusion [67J, but not those described for bolus injections [68].…”
Section: Molecular Biology and Biochemistry Of Urosupporting
confidence: 82%
“…The rate o f degradation o f URO is signif icantly lower than that o f CDD/ANP-99-126. a result which was confirmed by other groups [64.66] 58] These investigations may explain the differences o f tile in vivo kinetics between the two main A-type NPs. These differences, however, concern results described for long-term infusion [67J, but not those described for bolus injections [68].…”
Section: Molecular Biology and Biochemistry Of Urosupporting
confidence: 82%
“…Our previous reports demonstrated that renal ANP mRNA is significantly enhanced and the elevation of urinary ANP excretion correlated well with urinary sodium excretion in diabetic rats (Shin et al 1997) and deoxycorticosterone acetate (DOCA)-treated rats (Lee et al 1996). These findings support the proposal that renal-synthesized natriuretic peptide may be related to the change in water-electrolyte balance (Greenwald et al 1991). In animals and humans with diabetes, alterations in extracellular and exchangeable sodium have been found (Ortola et al 1987, Allen et al 1990) and have been thought to lead to changes in plasma ANP A B C Figure 4 Representative autoradiographs (upper panels) of the amplification of CNP and -actin mRNA by RT-PCR followed by Southern blot analysis in the renal cortex (A), outer medulla (B) and inner medulla (C) from normal control (NC, n=8), diabetic (DM, n=8), insulin-treated diabetic (ITDM, n=7) and low salt diet-treated diabetic (LSD-DM, n=7) rats on the 60th day after administration of citric buffer or streptozotocin.…”
Section: Discussionsupporting
confidence: 70%
“…Among others, natriuretic peptides (NPs) and nitric oxide (NO) have been widely implicated in the regulation of urinary sodium excretion and glomerular filtration rate (GFR) [4,5] . Both NPs and NO induce the generation of 3 ,5 -cyclic monophosphate (cGMP), in which the former activates the membrane-bound particulate guanylyl cyclase (GC) [6] and the latter activates thecytoplasmic soluble GC [7] .…”
Section: Introductionmentioning
confidence: 99%